1981
DOI: 10.3109/13813458109073997
|View full text |Cite
|
Sign up to set email alerts
|

Réactions cardio-vasculaires du rat à I'hypercapnie ventilatoire

Abstract: 1. Two populations of albino rats : normal and treated by phentolamine, or normal and vagotomized, have inhaled normoxic or hyperoxic mixtures with 3, 15 or 30% CO2 during 5 min. 2. Bradycardia is proportional to CO2 concentration, from 3% CO2. It is not suppressed by vagotomy. 3. Systemic arterial pressures, both systolic and diastolic, are decreased by 14% CO2. This hypotension is long lasting. At 30% CO2, immediate hypotension is followed by progressive recovery. After phentolamine, the return to normal is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…the renal vasodilatation is facilitated by inhibitory influences upon renal sympathetic activity. Taken together, the suggestions that the fall in Pa, c02 may exert a vasoconstrictor influence upon skeletal muscle, but a vasodilator effect on the kidney, are consistent with previous observations that the effects of a rise in Pa co2 in the rat depend upon the balance between vasodilator and vasoconstrictor influences (Lagneaux & Remacle, 1981;Hargreaves & Marshall, 1986).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…the renal vasodilatation is facilitated by inhibitory influences upon renal sympathetic activity. Taken together, the suggestions that the fall in Pa, c02 may exert a vasoconstrictor influence upon skeletal muscle, but a vasodilator effect on the kidney, are consistent with previous observations that the effects of a rise in Pa co2 in the rat depend upon the balance between vasodilator and vasoconstrictor influences (Lagneaux & Remacle, 1981;Hargreaves & Marshall, 1986).…”
Section: Discussionsupporting
confidence: 90%
“…This would be in accord with our previous evidence that the tachyeardia observed in hypocapnic hypoxia is largely due to increased sympathetic activity (Marshall & Metcalfe, 1988 b). However, another possibility is that tachycardia produced by the direct influence of a fall in Pa co2 upon the cardiac pacemaker plays a part, given the fact that the opposite effect predominates in the rat when Pa c°2 is raised (Lagneaux & Remacle, 1981;Hargreaves & Marshall, 1986). In summary, the present study suggests that the hypocapnia that accompanies the hyperventilatory response to systemic hypoxia substantially attenuates the hyperventilation by reducing the stimulation of peripheral and central chemoreceptors.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Since, when the vagi were intact but ventilation held constant, the response evoked by chemoreceptor stimulation was reversed to bradycardia, it may be concluded that influences other than lung stretch receptors but which are secondary to hyperventilation can induce tachycardia, although the primary cardiac response is bradycardia as in other species (see Daly, 1984). Given that a rise in Pa co2 induces bradycardia in the rat, apparently by a direct action on the heart (Lagneaux & Remacle, 1981;Hargreaves & Marshall, 1986), those secondary influences could have included the direct effect of a fall in PaC002 resulting from hyperventilation, and possibly a reflex initiated by atrial stretch receptor stimulation caused by a respiratory-dependent increase in venous return (see Daly, 1984). The fact that the baseline level of heart rate was not always reduced by guanethidine may indicate that this drug was not fully effective in blocking cardiac sympathetic activity; however, the observation that after guanethidine when the vagi were intact, chemoreceptor stimulation evoked bradycardia, supports the idea that the primary response was vagally mediated and suggests that effects secondary to hyperventilation were predominantly mediated by sympathetic fibres.…”
Section: Group IImentioning
confidence: 99%